CLINICAL PECULIARITIES OF DEPRESSIVE DISORDERS IN ELDERLY PATIENTS - Shadmanova, L.; Ashurov, Z.Sh.; Yadgarova, N.F.; Lyan, E.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Last decades approaches to an assessment of an outcome of depressive distress at persons of serotinal age have undergone essential changes. Along with conservation of traditional methodology in definition of categories of an outcome of depression and their division into the congenial and unfavorable bunches, represen-tation about criteria of reference of each concrete variant of an outcome to one of these categories has extended. The problem of an assessment of a depression at elderly patients gets the special practical importance in the light of traceable in the world of tendencies of augmentation of centre lifetime with conservation of high social activity and working capacity of the person. And also, the factor of "rare hospitalizations" (29.5%) as a predisposing and provoking one. We believe that the most specific factor for this group is the gradual onset of the disease, which characterizes the development of somatic suffering in "endogenous" patients. The development of the disease imperceptible for patients means for them an untimely initiation of therapy, a worse somatic prognosis and a persistent chronic stress factor. Such a judgment can be considered typical: "it hurts slightly - I endure it; I wait for it to pass by itself."